2017
DOI: 10.1515/orga-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Older and Younger Employees – The Case of Slovenia

Abstract: Background and Purpose:People spend a significant part of their lifespan working, but the role of age in job design and implementation of work have largely been ignored. The consequences can be evident in stress and burnout in different symptoms. Thus, age-diverse employees are faced with different symptoms of burnout and stress when carrying out their work. The main aim of this paper is to present burnout of older employees compared to younger employees in Slovenian companies. Design/Methodology/Approach: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
10
0
5
Order By: Relevance
“…Items for the organisation climate component employee motivation were formed by authors Islam and Ismail (2008) and are in line with recognitions of Bhatti et al (2016) and May et al (2004). Items for the dependent component employee engagement were formed by authors Robinson et al (2004) and Gallup (2006). Also those items we combined and also other authors support their findings, e.g.…”
Section: Sample and Measuresmentioning
confidence: 99%
“…Items for the organisation climate component employee motivation were formed by authors Islam and Ismail (2008) and are in line with recognitions of Bhatti et al (2016) and May et al (2004). Items for the dependent component employee engagement were formed by authors Robinson et al (2004) and Gallup (2006). Also those items we combined and also other authors support their findings, e.g.…”
Section: Sample and Measuresmentioning
confidence: 99%
“…Further, poor health diminishes work productivity and satisfaction (O'Neil, 2017). We can conclude from the stated that flexible working hours are more and more important for employees, as they enable them to maintain a balance between professional and personal life, do not lead to exhaustion at work or deterioration of the health of older employees (Rožman et al, 2017a). Bizjak (2014) explains that targeted programs for enhancing the health of employees and improvement of working conditions bring numerous benefits to work organizations, which relate to greater safety in the workplace, lower risk of injuries at work, better health and well-being of employees, lower costs of sick leave, greater productivity, satisfaction, etc.…”
Section: 4mentioning
confidence: 99%
“…Research by Rožman et al (2017), which found differences in burnout symptoms between younger (18 to 49 years) and older (50 to 65 years) employees in different Slovenian work organizations (n = 400), showed that older employees are more susceptible to physical symptoms of burnout. The authors also point out that reduced work capacity is associated with high physical workloads.…”
Section: Agementioning
confidence: 99%
“…It is also important to assemble work teams that are multi-generational. According to Rožman et al (2017), it is important for managers to be aware of the age diversity of their employees and their needs.…”
Section: Agementioning
confidence: 99%